Modernisasi Pendidikan melalui Implementasi Manajemen Mutu di Kalangan Pesantren Nahdhatul Ulama di Madura - Saadatul Ummah, Fiena (NAHNU: Journal of Nahdlatul Ulama and Contemporary Islamic Studies, 2023)
Pondok Pesantren is an Islamic religious educational institution that grows and is recognized by the Madurese community from time to time. Islamic boarding school education in Amdura, which initially tended to be oriented towards deepening religious knowledge, as the era progressed, the Islamic boarding school began to rejuvenate or modernize, carry out new management and integrate general science material (science and technology) into the daily education system. The pesantren organization in Madura is structured in such a way with various tasks carried out in various organizational fields. Islamic boarding schools as organizations implement strong leadership and healthy management under the charismatic character and figure of Kyai as the leader of the Islamic boarding school. The figure of a leader in an Islamic educational institution is a guide that will be able to bring the institution to rapid progress and development. Pondok pesantren merupakan suatu lembaga pendidikan agama Islam yang tumbuh dan diakui oleh masyarakat Madura dari waktu ke waktu. Pendidikan pesantren di Madura yang mulanya cenderung berorientasi pada pendalaman ilmu agama, seiring berkembangnya waktu dirinya (pesantren) mulai melakukan peremajaan atau modernisasi, melakukan manajemen mutu dan mengintegrasikan materi ilmu pengetahuan umum (sains dan teknologi) ke dalam sistem pendidikan sehari-hari. Organisasi pesantren di Madura disusun sedemikian rupa dengan berbagai tugas yang dijalankan di berbagai bidang organisasi. Pondok pesantren sebagai organisasi menerapkan kepemimpinan yang kuat dan manajemen yang sehat di bawah ketokohan dan figur karismatik kiai selaku pimpinan di pondok pesantren. Figur seorang pemimpin dalam sebuah lembaga pendidikan Islam menjadi pedoman yang mampu membawa lembaga tersebut mengalami kemajuan dan perkembangan pesat dari waktu ke waktu.